Il contributo della Chiesa irlandese alla Fase 1 del Sinodo dei Vescovi sulla Sinodalità e l’inizio del cammino sinodale nazionale (Stato, Chiese e pluralismo confessionale, 2025)
The Contribution of the Catholic Church in Ireland to Phase 1 of the Synod of Bishops on Synodality and the Beginning of the Irish Synodal PathwayABSTRACT: The Catholic Church saw the opening of the synodal process for the celebration of the Synod of Bishops on Synodality on October 8-10, 2021, the second and final session of which took place on October 2024. The synodal process of the universal Church has intertwined with the national synodal pathway undertaken by the Irish Catholic Church, which intends, after the Synod of Bishops on Synodality has ended, to continue the journey of prayer, listening and discernment, to be carried out in the same synodal “style” as the Synod of Bishops, benefiting from the stimulus and reflections of the latter. This article focuses on the documents produced by the Irish Catholic Bishops' Conference in the context of the first phase of the universal synodal process and the national synodal journey and, within these, specifically on some issues that have particularly marked the experience of the Catholic Church in Ireland in recent times, like the sexual abuses of clergy or the status of women in the Church.SOMMARIO: 1. Introduzione - 2. Il Sinodo dei Vescovi - 3. Un cammino sinodale per l’Irlanda - 4. La consultazione del Popolo di Dio - 5. Il rapporto di sintesi irlandese - 6. Alcune reazioni alla sintesi irlandese - 7. Conclusioni.